Edukasi Pemanfaatan Limbah Cair Tahu Menjadi Kerajinan Tangan Di Desa Mangunjaya, Bekasi - Tulus Sukreni; Ismaniah Ismaniah; Dinda Yesika Agustian; Rizky Yusrina Amalia; Bungaran Saing (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Desa Mangunjaya is one of the tofu producers in Bekasi. Tofu is a soy-based food that is usually produced by household industries using traditional technology, which currently experiencing environmental problems with inadequate waste disposal. Production activities from the tofu industry will certainly produce solids and wastewater. These wastes can harm the environment. Tofu wastewater contains very high organic compounds and nutrients so that it can be recycled to produce other useful products. Therefore education was held for residents around the tofu factory regarding the utilization of tofu liquid waste into handicrafts by processing the liquid waste into nata de soya first. The method used in this education is to provide information and explain the stages of manufacturing. The purpose of education is to explain to residents so they can process tofu wastewater into goods that have a sale value, beside that residents can know the importance of processing waste so it does not cause environmental pollution. The result of education is that residents understand the use of tofu liquid waste and the program implemented has succeeded in achieving the expected goals.